Iron status in intrauterine contraceptive device users - Wahda B. Al-Youzbaki; Luma S. AL-Nuri; Janan Gazzi (University of Mosul, 2008)
The objective of this study is to evaluate the effect of one year use of Copper-T380A intrauterine contraceptive devices (IUCDs) on iron status of the body. It represent a Cohort study that was carried at Family Planning Center in AL-Batool Teaching Hospital, during the period from April 2006 - August 2007. Thirty women enrolled in this study, age ranged between 20-42 years, and with initial level of hemoglobin (Hb) ≥ 10 g/dl, were followed up at the time just before the insertion, then after 6 months and one year of the insertion of the IUCDs. Another thirty healthy women age ranged between 20-43 years who did not use neither hormonal contraceptives nor IUCDs were considered as a control group, all followed by measuring Hb level and PCV by Cyanomethaemoglobin method , serum iron and total iron binding capacity (TIBC) using Enzymatic Calorimetric method and percent iron saturation was calculated by equation. The results of this study showed that IUCDs caused a significant decrease in the mean serum level of Hb, PCV and iron among the IUCDs users after 6 months and one year of the insertion of the IUCDs compared with the initial serum level at the time of the insertion. But a significant decrease in TIBC and % saturation only after one year of the insertion of the IUCDs. Also there were a significant decrease in mean serum Hb and % saturation of the IUCDs users after 6 months in comparison with the non users, while a significant decrease in all the iron status parameters of IUCDs users after one year in comparison with the non users. There were no significant difference between the iron status parameters of IUCDs users in relation with number of children the IUCDs users have delivered. This study concluded that the Copper-T380A IUCDs use for one year cause a significant decrease in the iron status parameters, which is more with the increase duration of use but not affected by the number of children of the users of the IUCDs. It is recommended that iron supplementation, be a part of the IUCDs services provided in Family Planning Centers in the view of the high prevalence of anemia among women in child bearing age in Iraq.